Effect of infectious bursal disease (IBD) vaccine on Salmonella Enteritidis infected chickens. Issue 29 (22nd June 2017) - Arafat, Nagah; Eladl, Abdelfattah H.; Mahgoub, Hebatallah; El-shafei, Reham A.
Highlights: Effect of IBD vaccine (228E®) on S. Enteritidis infected chickens was indicated. The recorded mortalities were higher in the 228E® + SE infected group. The anti- S. Enteritidis antibody titres were higher in the SE infected group. The 228E® + SE group had higher bursal lesion scores than the SE infected group. Chickens given IBDV vaccine failed antibody response to the S. Enteritidis. Abstract: Background: Chickens infected with both infectious bursal disease virus (IBDV) and Salmonella had higher mortality. In this work, we investigated the effect of IBDV vaccine (modified live-virus bursal disease vaccine, Nobilis strain 228E®) on experimentally infected chickens with Salmonella Enteritidis (SE). Methods: Four experimental groups were included in this study, negative control group, 228E®group, 228E® + SE infected group, and SE infected group. Chickens were ocularly administrated 228E® at 12 days of age and orally infected with S. Enteritidis at 13 days of age. Sera, intestinal fluid, blood, cloacal swabs and tissue samples were collected at 1, 2 and 3 weeks post vaccination (PV). Results: The recorded mortalities were higher in the 228E® + SE infected group, compared to the SE infected group. The anti- S. Enteritidis serum antibody titer and the intestinal mucosal IgA level were higher in the SE infected group at 2 and 3 weeks PV, compared to 228E® + SE infected group. S. Enteritidis fecal shedding and organ colonization were significantly higher in the 228E® + SE infected group than the SE infected group at 2 and 3 weeks PV. The 228E® + SE group had significantly lower bursa to body weight ratios at 2 and 3 weeks PV, as well as had higher bursal lesion scores than the SE infected group. IBDV vaccine depressed the specific-SE systemic and mucosal antibody responses, but did not affect the specific-SE cellular immune responses. Conclusion: Chickens administrated IBDV vaccine, followed by S. Enteritidis infection, could cause a significant effect on the bursa of Fabricius, resulting in failure of systemic and mucosal antibody responses to the S. Enteritidis and reduce the elimination and the clearance of S. Enteritidis.